TEXTUAL EQUIVALENCE OF PHRASAL VERB TRANSLATION IN THE NOVEL ‘THE OTHER SIDE OF MIDNIGHT’ INTO ‘LEWAT TENGAH MALAM’ - Permatasari, Anita (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 22 (2015): September 2015, 2015)
In transferring one language into another, translation is much needed by someone to solve diversity problems in languages either from lexical or grammatical problems. Lexical related to the terms used in the text, and grammatical problems cover the problems related to the word in relation to the other word. The lexical problems in case of variable of phrasal verb will be analyzed by knowing types of phrasal verb with the theory of equivalence in translation in which each language also has its own language system which is different one another besides cultural divergence. In finding the textual equivalence, having the same and different concepts in both SL and TL are applied. The combination between verb and particle in phrasal verb can form many various meaning in which the meaning itself can predicted or can’t be predicted from the individual meaning of phrasal verb. Those combinations give something unique and special in form of verb, adjective, or adverb in a sentence.
Keywords: phrasal verb, translation, equivalence